Aplikasi Pencatatan Kalori Harian Berbasis Android Dengan Arsitektur MVVM - Ulhaq, Alfi Zia; Adilukito, Abilawa Zulfiqar; Neru, Sultan Muhamad Pascal Gadja; Agisfio, Muhammad Daffa (Computer Science (CO-SCIENCE), 2025)
An imbalance between calorie intake and expenditure is considered the main cause of obesity or being overweight. So by controlling your calorie intake in a balanced manner and according to your needs you will be able to prevent obesity. The daily calorie recording application can help someone record, control and obtain information on their calorie intake. This article discusses the development of this type of application, named Nutrizen, using the waterfall method, during the development process by the CH2-PS076 team in the Bangkit 2023 batch 2 program. The application created is an Android-based application created with the Kotlin programming language and MVVM architecture as a design pattern that is easy to learn and makes the code easy to understand and manage. Testing this application uses the usability test method with the System Usability Scale tool to determine the level of user acceptance of usability. The results obtained include a marginal level of usability acceptance, so improvements are needed so that this application can be more accepted and relied on by the wider community.